Topochemical intercalation reactions of ZrSe3 - Elgaml, M; Cassidy, S; Clarke, S (Elsevier, 2022)
Intercalation of alkali and alkaline earth metals into ZrSe3 via soft chemical routes injects electrons and has a significant effect on the selenide-selenide bonding. K, Rb and Cs intercalates of ZrSe3 prepared at low temperatures (-78 °C) from metal ammonia solutions contrast with related polymorphs obtained at high temperature (850 °C). KxZrSe3 synthesised at low temperatures crystallises in orthorhombic Cmc21, while the polymorph obtained at high temperatures crystallises in Immm. The two structures prepared under drastically different conditions differ by relative shifting of ZrSe3 layers. In contrast, CsxZrSe3 shows the Immm polymorph at low temperature and the Cmc21 polymorph at high temperatures, while a single RbxZrSe3 polymorph in Immm is formed at both temperatures. Intercalation of Ca from liquid ammonia facilitates the co-intercalation of the solvent because of the strong solvation of Ca2+ . This compound has severe faulting due to the flexibility in the relative shifts of adjacent ZrSe3 layers.